Правовий статус реабілітаційних закладів в Україні - Івахненко, О. А.; Ivakhnenko, O. A. (Вісник Кримінологічної Асоціації України. - 2024. - № 1 (31). - С. 691-702, 2024)
Статтю присвячено особливостям правового статусу реабілітаційних закладів в Україні. Досліджено законодавчі та підзаконні акти, які встановлюють вимоги до реабілітаційних закладів, особливості їх діяльності та управління ними. Вказано, що правовий статус реабілітаційного закладу – це встановлений нормами права особливий порядок створення, ліцензування, акредитації, здійснення господарської діяльності, користування майном, кадрового і матеріально-технічного забезпечення таких закладів.

The scientific article is devoted to the peculiarities of the legal status of rehabilitation institutions in Ukraine. Legislative and subordinate acts that establish the requirements for rehabilitation institutions, the specifics of their activities, and management have been studied. The works of scholars in the fields of jurisprudence, public administration, and medicine, who have researched the legal status of healthcare institutions, the essence of rehabilitation services, and the activities of rehabilitation institutions, have been examined. It is noted that the legal status of a rehabilitation institution is a special order established by law for the creation, licensing, accreditation, business activities, use of property, and staffing and material-technical support of such institutions. It is concluded that rehabilitation institutions of communal or state ownership are established in the form of establishments. Rehabilitation institutions of private ownership can be established in the organizational-legal form of business companies or private enterprises. Prosthetic and orthopedic enterprises can be established based on state, communal, or private ownership. Rehabilitation institutions are a type of healthcare institution that provides rehabilitation services based on a license for medical practice business activities. Licensing conditions establish the material-technical, staffing, and organizational requirements for obtaining a license for medical practice business activities related to rehabilitation services. Rehabilitation institutions can be established in the forms of rehabilitation hospitals, medical-rehabilitation centers, and outpatient rehabilitation institutions. Proposed amendments to the current legislation are suggested. Proposals for future scientific research in this field are expressed.

Статья посвящена особенностям правового статуса реабилитационных учреждений в Украине. Исследованы законодательные и подзаконные акты, устанавливающие требования к реабилитационным учреждениям, особенности их деятельности и управление ими. Указано, что правовой статус реабилитационного учреждения – это установленный нормами права особый порядок создания, лицензирования, аккредитации, осуществления хозяйственной деятельности, пользования имуществом, кадрового и материально-технического обеспечения таких заведений.
Legal status of rehabilitation institutions in Ukraine
Keywords: реабілітація; реабілітаційний заклад; реабілітаційна допомога; реабілітаційна послуга; правовий статус; правове регулювання; охорона здоров’я; медична допомога; пацієнт; ліцензійні умови; ліцензування; акредитація; господарська діяльність; rehabilitation; rehabilitation institution; rehabilitation assistance; rehabilitation service; legal status; legal regulation; healthcare; medical assistance; patient; licensing conditions; licensing; accreditation; business activities; реабилитация; реабилитационное заведение; реабилитационная помощь; реабилитационная услуга; правовой статус; правовое регулирование; здравоохранение; медицинская помощь; пациент; лицензионные условия; лицензирование; аккредитация; хозяйственная деятельность